Clinical clearance of the thoracic and lumbar spine: a pilot study. Issue 6 (13th May 2019) - Mitra, Biswadev; El‐Menyar, Ayman; Mercier, Eric; Liew, Susan; Varma, Dinesh; Fitzgerald, Mark C.; Al‐Hilli, Shatha; Peralta, Ruben; Al‐Thani, Hassan; Cameron, Peter A.
Abstract : Background: In patients who are awake with normal mental and neurologic status, it has been suggested that the thoracolumbar (TL) spine may be cleared by clinical examination, irrespective of the mechanism of injury. The aim of this pilot study was to test the feasibility and accuracy of a clinical decision tool focused towards clearance of the TL spine during assessment of patients in the emergency department after trauma. Methods: A prospective interventional study was conducted at two major trauma centres. The intervention of a clinical decision tool for assessment of the TL spine was applied prospectively to all patients with subsequent imaging results acting as the comparator. The primary outcome variable was fracture of the thoracic or lumbar vertebra(e). The clinical decision tool was assessed using sensitivity and specificity for detecting a TL fracture and reported with 95% confidence intervals (CIs). Results: There were 188 cases included for analysis that all underwent imaging of the thoracic and/or lumbar vertebrae. There were 34 (18%) patients diagnosed with fractures of the thoracic and/or lumbar vertebrae. In this pilot study, sensitivity of the clinical decision tool was 100% (95% CI 87.3–100%) and specificity was 37.0% (95% CI 29.5–45.2%) for the detection of a thoracic or lumbar vertebral fracture. Conclusions: Feasibility of clinical clearance of the TL spine in two major trauma centres was demonstrated in a clinical study setting. Evaluation of this clinical decision tool in patients following blunt trauma, particularly in reducing imaging rates, is indicated using a larger prospective study. Abstract : This pilot study was to test the feasibility and accuracy of a clinical decision tool focused towards clearance of the thoracolumbar spine during assessment of patients in the Emergency Department after trauma. In this pilot study, sensitivity of the clinical decision tool was 100% (95% confidence interval: 87.3–100%) for the detection of a thoracic or lumbar vertebral fracture.